(3QMdI Gdefi hGdefIs - (3CMeO Hf GdeUWaj Hf WhjQ GdLfI,J (B1256 (3g` s ((3Sgd Hf CHj s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf fMeOg Ydi aQU GdML Ydi GdeDefjf , djWhahG ehGbHJ jhe GdML GdCcHQ hHYO ajbhd GdWGdH CMeO NQLfG ef JjTjJ jhe GdNejS , hfYfi HPdc Gdjhe GdPi NQL ajg GdeUWai dMLI GdhOGY jhe GdNejS , hgh jhe NQhLfG fMfs
(3BNQgG (B:s
(3aHjfeG fMf YfO ChdGO CQejTi EP LGAge HYV CScGQf ef CQV hGOfhf Ke QLYfG Edi cJHfG hNjdfG h NQLfG ef hGOfhf hecKfG Hjf hGOfhf hhGOGf QLHnG hTYHGf Zdi KdGK djGd , hbOefG eMQhSI hGOGf s
(3HgG fXGe GdJYbjHIs
(3fSNI ecJhHI HWQjbI afjIs
(3hGdSWhQ ajgG eJLgI Edi GdCYdi s
(3eQbeI GdUaMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs